Experimental Study on the Removal Process of Cobalt from Fly Ash using Different Solvents - M. Ali, Israa Shakir (Nahrain University College of Engineering Journal, 2014)
In fly ash of thermal power plant, there are plenty of valuable metals, such as nickel, cobalt, iron. Recovery of valuable metals from fly ash not only protects the environment but also improves the utilization of resources. This study investigates the leaching process of cobalt from fly ash. A two-level three-factor full factorial design was successfully employed for experimental design and analysis of the results. The combined effects of type of solvent, concentration of solvent, time of stirring and temperature on the removal of cobalt were assessed using response surface methodology. The results showed that the maximum yield of cobalt 93% was obtained using 6 M hydrochloric acid as leaching solvent, at time of 68 min. and 45° C temperature.